Benefits of internationalisation for acquirers and targets - But unevenly distributed - Rainer Frey; Stefan Goldbach (Deutsche Bundesbank, 2021)
In some countries around the world, the advantages of globalisation have been increasingly called into question recently. In particular, takeovers by foreign firms raise suspicions of technology theft and job cuts at the newly acquired local plant. By looking at Germany, as a large open economy, between 1999 and 2018 we first see that both German firms that are acquired by foreign investors and German firms which invest abroad show similar characteristics: they are on average larger, more innovative and productive, but less profitable than purely national firms. With internationalisation, a variety of positive effects emerge. With respect to takeovers of German companies by foreign investors, the productivity and sales of the German affiliate increase while the foreign owners tend to step up expenditure on the labour force in Germany in the aftermath of the acquisition - compared to purely domestically owned firms. In the case of German firms going international, we find positive productivity and sales effects for relatively small companies investing abroad, and this internationalisation is not to the detriment of the domestic labour force. Thus, all in all, this supports a positive view of globalisation. However not all firms benefit: in particular, sector, firm size and time horizon have a bearing on the outcome.
Keywords: D22; D24; F23; G34; 330; globalisation; firm acquisition; M&A; productivity; sales; innovativeness; know-how; technology; labour costs; employment; wages; firm heterogeneity